Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.ehb.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Measures of the intergenerational transmission of body mass index between mothers and their children in the United States, 1981–2004

Abstract: This research provides estimates of the intergenerational persistence of Body Mass Index (BMI) between women and their children when both are at similar stages of the lifecycle. Using data from the National Longitudinal Survey of Youth 1979 (NLSY79) and the Young Adults of the NLSY79, associations between the weight status of women and their children are measured when both generations are between the ages of 16 and 24. In the entire sample, the measured intergenerational correlation of BMI is significantly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 43 publications
7
67
0
Order By: Relevance
“…In their paper entitled 'Parental and offspring adiposity associations: insights from the 1958 British birth cohort' , Power et al (2011) use the rich and extensive dataset collected from members of the Medical Research Council (MRC) 1958 birth cohort of UK children, and from their parents and offspring, to investigate parentoffspring weight status associations over the lifecourse, and how they vary across generations. They confirm a previous observation showing that the correlation between BMI in parents and offspring persists into adulthood (Classen 2010) and also demonstrate a correlation between parental BMI in childhood and offspring BMI. They show that parentoffspring correlations in BMI were stronger for recent rather than for older generations.…”
Section: Obesity Patterning Within Familiessupporting
confidence: 91%
See 1 more Smart Citation
“…In their paper entitled 'Parental and offspring adiposity associations: insights from the 1958 British birth cohort' , Power et al (2011) use the rich and extensive dataset collected from members of the Medical Research Council (MRC) 1958 birth cohort of UK children, and from their parents and offspring, to investigate parentoffspring weight status associations over the lifecourse, and how they vary across generations. They confirm a previous observation showing that the correlation between BMI in parents and offspring persists into adulthood (Classen 2010) and also demonstrate a correlation between parental BMI in childhood and offspring BMI. They show that parentoffspring correlations in BMI were stronger for recent rather than for older generations.…”
Section: Obesity Patterning Within Familiessupporting
confidence: 91%
“…Epidemiological data provide mounting evidence that in affluent western societies there are positive associations between the levels of obesity of parents and their offspring (Reilly et al 2005;Lawlor et al 2006;2008;Davey Smith et al 2007;Kivimäki et al 2007;Classen 2010;Labayen et al 2010). In the UK, Whitaker et al (2010) used data from The Health Survey for England 2001England -2006 to demonstrate a greater risk of obesity, as measured by body mass index (BMI), among children of overweight and obese parents.…”
Section: Obesity Patterning Within Familiesmentioning
confidence: 99%
“…Other papers examine only the tendency to obesity (as a limited binary outcome) between generations and not the IBE or IBC (Martin 2008). A significant departure from the epidemiological literature this was first provided by Classen (2010). Using data from the National Longitudinal Survey of Youth 1979 (NLSY 1979) and the Young Adults of the NLSY79, he estimates the intergenerational transmission of BMI between children and their mother when both generations are between the ages of 16 and 24.…”
Section: The Intergenerational Transmission Of Health Attributesmentioning
confidence: 99%
“…Research has revealed a modest within-family parent-child BMI correlation of between 0.25 and 0.35; there appears to be a stronger relationship between mother and child BMI than between father and child. [1][2][3][4] Both parents being overweight or obese increases a child's obesity risk, 5 and adult BMI is independently associated with offspring BMI in both the adult's childhood and adulthood, suggesting multi-generational transfer. 6 Compared with the parent-child obesity link, documentation of a sibling obesity association has been inconsistent.…”
Section: Introductionmentioning
confidence: 99%